The Lives of Monastic Reformers, 2 : Abbot Vitalis of Savigny, Abbot Godfrey of Savigny, Peter of Avranches, and Blessed Hamo - Sauvage, E. P.; Sauvage, E. P.; Pepin, Ronald; O'Brien, Maureen M.; Feiss, Hugh (Book collections on Project MUSE., 2014)
"This volume offers translations of the twelfth-century Latin vitae of four monks of the Monastery of Savigny: Abbot Vitalis, Abbot Godfrey, Peter of Avranches, and Blessed Hamo. Founded in 1113 by Vitalis of Mortain, an influential hermit-preacher, Savigny expanded to a congregation of thirty monasteries under his successor Godfrey (1122-1138). In 1147, the entire congregation joined the Cistercian Order. Around 1172, two monks of Savigny, Peter of Avranches and Hamo, friends but very different personalities, died. Their stories were told in two further vitae. The vitae of these four men exemplify the variety of people and movements found in the monastic ferment of the twelfth century."--